In silico characterisation and catalytic property analysis of L-2-Haloacid dehalogenase (DEHL) from rhizobium SP.RC1 - Aliyu Adamu, 1986- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2018